Phenotypic plasticity in the ovarium of crested flower of Hibiscus rosa-sinensis - SAIFUDIN SAIFUDIN; ANDI SALAMAH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Saifudin, Salamah A. 2019. Phenotypic plasticity in the ovarium of crested flower of Hibiscus rosa-sinensis. Biodiversitas 20: 1241-1247. Hibiscus rosa-sinensis L. or known as Kembang Sepatu in Indonesia has a variety that is very diverse for the shape of flowers, sizes, and colors. Variations of Hibiscus rosa-sinensis L. flowers not only can be observed among its hybrids but also in one hybrid. The hybrid is known as a crested flower (double type I), one of four categories of H. rosa-sinensis flower shapes in nature. This study aims to know the variation of the crested flower through morphological and anatomical observations of its ovaries. The morphological observation was carried out by observing ovarian outer surface under the Dino-Lite microscope. An anatomical observation was done by observing the longitudinal section (l-s) of fresh ovarian samples under a light microscope with 4x magnification. Morphological observation of 200 samples showed three types of external structure of ovaries: non-twisted ovary, twisted ovary, and ovary with its wall forming a structure like a petal. Anatomical observation of 137 samples showed three types of ovaries: normal ovary, ovary with its internal undergo a change or a reduction, and ovary with a formation of pistillum-like structure. Variations that occur indicate plasticity phenomenon in crested flowers. Further research is needed to find out the main factors causing variations in crested flower ovaries.